Field Emission Scanning Electron Microscopy New Perspectives for Materials Characterization - Brodusch, Nicolas (SpringerBriefs in Applied Sciences and Technology,, 2018)
This book highlights what is now achievable in terms of materials characterization with the new generation of cold-field emission scanning electron microscopes applied to real materials at high spatial resolution. It discusses advanced scanning electron microscopes/scanning- transmission electron microscopes (SEM/STEM), simulation and post-processing techniques at high spatial resolution in the fields of nanomaterials, metallurgy, geology, and more. These microscopes now offer improved performance at very low landing voltage and high -beam probe current stability, combined with a routine transmission mode capability that can compete with the (scanning-) transmission electron microscopes (STEM/-TEM) historically run at higher beam accelerating voltage.